The Influence of Service Quality and Teacher Performance on Student Satisfaction with Administrative Services - Alifani Nur Indah Sari; Muh. Nasrullah; Nasir Nasir (Journal of Educational Development and Learning (JEDAL), 2024)
Student satisfaction represents something that is very useful in achieving school targets, for this reason school principals must pay attention to the quality of service and teacher performance because both are able to provide services for students to feel and see. The aim of this research is to determine the influence of service quality and educator performance on student satisfaction with administrative services at SMA Plus Budi Utomo Makassar. This research is included in descriptive research with a quantitative approach. The sample in this study was 103 students at SMA Plus Budi Utomo Makassar using a simple random sampling technique. In this research, data collection techniques used were observation, questionnaires, interviews and documentation. Meanwhile, the various data analyzes in this research used descriptive statistical analysis, classical assumption tests, hypothesis tests and multiple linear regression. The results of the research explain that the service quality variable is at a good level, while the teacher performance variable is at a very good level, and the student satisfaction variable is at a very good level. Based on the results of the correlation test, the two variables, namely service quality and student satisfaction, have a moderate relationship, while the two variables, namely teacher performance and student satisfaction, do not have a significant relationship. Based on the partial test results, it was concluded that there was a positive and significant influence on service quality on teacher performance, and no positive and significant influence on teacher performance on student satisfaction at SMA Plus Budi Utomo Makassar. Meanwhile, service quality and teacher performance simultaneously influence student satisfaction.